The glycemic/metabolic responses to meal tolerance tests at breakfast, lunch and dinner, and effects of the mitiglinide/voglibose fixed-dose combination on postprandial profiles in Japanese patients with type 2 diabetes mellitus. (February 2014) - Ono, Yuri; Nakamura, Akinobu; Yong Cho, Kyu; Nomoto, Hiroshi
<x xml:space="preserve">Abstract</x> Background: Meal tolerance tests (MTTs) are usually conducted at breakfast after overnight fasting in type 2 diabetes mellitus (T2DM) patients, but differences in postprandial glycemic responses between meals have been reported. Objective: We conducted MTTs at breakfast, lunch, and dinner to examine the effects of a fixed combination of 10 mg mitiglinide/0.2 mg voglibose (the combination) on glycemic/metabolic responses to meals during the day in T2DM patients. MTTs with unified meals were conducted in 11 T2DM patients before and after 4 weeks of treatment with the combination administered thrice daily before meals. Glycemic/metabolic profiles measured before and at 30, 60, and 120 min after each meal were compared between each meal and between the baseline and treatment periods. Results and conclusion: The combination significantly reduced postprandial hyperglycemia after each meal. Postprandial AUC0 – 120 min for insulin significantly decreased after lunch and dinner compared with after breakfast, while insulin levels significantly increased at only 30 min after breakfast and dinner. The combination also significantly increased postprandial C-peptide and active glucagon-like peptide-1 levels, and reduced free fatty acid and triglyceride levels, but did not significantly affect glucagon levels compared with baseline, confirming that treatment with the combination improves postprandial responses in Japanese T2DM patients.